EFEKTIFITAS MEDIA GEOBOARD TERHADAP HASIL BELAJAR MATEMATIKA MATERI KELILING DAN LUAS BANGUN DATAR KELAS 3 - Muhammad Ferry Nugroho; Wulan Sutriyani (EMTEKA: Jurnal Pendidikan Matematika, 2024)
T This research aims to determine the effectiveness of using geoboard learning media in mathematics learning about the circumference and area of flat shapes carried out in class 3 at SDN 2 Guyangan, namely by increasing student learning outcomes. This type of research is experimental research with a Pre-Experimental Design One-Group Pretest-Posttest design. using three treatments. The population is all 19 class 3 students, then the sample used a saturated sample model which was also taken from all 19 class 3 students. The data collection instrument in this study used a mathematics test in class 3, which resulted in the following results: studying using geoboard media obtained an average score of 79.79 and without using geoboard media obtained an average score of 43.58. The difference in average value before using and after using the media is 36.21. paired sample t-test obtained t-value = 9.456. At the real significance level = 0.05, the t-table value = 2.101 with df = 18. This shows that t-count > t-table, so that H0 is rejected and H1 is accepted. This shows that there are differences in learning outcomes before and after using geoboard media and shows that geoboard media is effective in the mathematics learning outcomes of class 3 students at SDN 2 Guyangan.